Postural stress and risk conditions in manual load handling of Chilean industrial workers - Urrejola-Contreras, Gabriela P.; Pérez-Casanova, Daniela C.; Pérez-Lizama, Miguel A.; Zambra, Boris Gary (International Journal of Occupational Safety and Health, 2023)
Introduction: Although, there is a current regulatory framework for optimal manual handling of loads to preserve health conditions in the industrial sector, technical assessment and the use of certain instruments are still required for the diagnosis of occupational hazards. This study aimed to identify the occupational hazards associated with manual load handling in industry workers and estimate those resulting from postural stress.Methods:  Fifty-two (52) industry workers took part in this cross-sectional study. All participants were evaluated using the Manual Handling Guide and the Reba assessment tool.  Subjects were characterized, and risks associated with different tasks were detected.Results: 59.6% of workers were between 18 and 45 years old. Lifting, lowering, and transporting loads activities had a repetitive task risk of 94%, exceeding the weight limit in 85.7% of cases. Pushing and pulling activities, mostly showed a working postural risk of 82% and a high perception of initial effort (Borg> 8). Reba score warned to intervene immediately in both types of tasks.Conclusion: Risk from the manual handling of loads found in this study constitutes an alert that suggests reviewing compliance with the current regulation, as well as effective use of working pauses and the improvement of strategies to minimize physical efforts used by workers.